Clinicopathological Parameters Related to Malignant Transformation of Oral Leukoplakia: A Meta-Analysis - Cristina Fuentes-perez; Alberto Rodriguez-archilla (Cumhuriyet University, 2021)
Objective. To assess the clinical-pathological factors related to the malignant transformation of oral leukoplakia. Materials and Methods. A search for articles on malignant transformation factors related to oral leukoplakia was conducted in the following electronic databases: PubMed (MEDLINE, Cochrane Library), Web of Science (WoS) and Google Scholar. Thirty-seven articles with a low-moderate risk of bias according to the Newcastle-Ottawa methodological quality scale were included in this meta-analysis. The data were analyzed using the statistical programs RevMan 5.4 (The Cochrane Collaboration, Oxford, UK) and MedCalc Statistical Software version 16.4.3 (MedCalc Software Ltd. Ostend, Belgium) programs. The estimated prevalence was calculated according to DerSimonian and Laird random method. For dichotomous outcomes, the estimates of effects of an intervention were expressed as odds ratios (OR) using the Mantel-Haenszel (M-H) method with 95% confidence intervals. Results. The estimated global prevalence of malignant transformation of oral leukoplakia was 9.15%. The factors with the highest malignant transformation risk of oral leukoplakia were: non-homogeneous clinical types (OR: 5.41; p<0.001); leukoplakias with moderate-severe dysplasia (OR: 3.43; p<0.001); lesions located on the tongue and/or the floor of the mouth (OR: 3.19; p<0.001); leukoplakias in non-smokers (OR: 2.08; p<0.001) and lesions in women (OR: 1.73; p<0.001). In contrast, older age or regular alcohol intake were factors without significant influence (p>0.05).Conclusions. Non-homogenous oral leukoplakias and with moderate-severe dysplasia are those with the highest probability of malignant transformation.